The homologous recombination protein RAD51 is a promising therapeutic target for cervical carcinoma - Qian Chen; Dongge Cai; Mu Li; Xiaoling Wu (2017)
RAD51 is one of the pivotal enzymes for DNA double-strand break (DSB) repair by the homologous recombination (HR) pathway, which implies it as a promising and novel target for cancer therapy. Recent findings have indicated RAD51 protein is overexpressed in a variety of tumors. The high-expression of RAD51 is related to poor prognosis. RAD51 is involved in the repair of DNA damage and the generation of genetic diversity by an evolutionarily conserved mechanism. However, the exact mechanism of Rad51 in the progression of cervical cancer remains unclear. RI-1 is a small molecule that inhibits the central recombination protein RAD51. In this study, we found that RAD51 was highly expressed in invasive squamous cervical cancer (SCC). The administration of RI-1 inhibited cell growth in vitro and reduced growth of tumor xenografts in vivo with cervical cancer cells (HeLa and SiHa). Further investigation suggested that RAD51 protein significantly promoted the cell cycle transition from the G0/G1 to S phase. In addition, the inhibition of RAD51 reduced the level of the cell cycle related protein cyclin D1, but increased the levels of p21 mRNA and protein. As a DNA DSB repair enzyme, the expression of RAD51 in tumor cells possibly affects their sensitivity to anti-cancer agents. Additionally, in experiments using cisplatin and ionizing radiation, RI-1 treated cervical cancer cells, HeLa and SiHa, were sensitized to a greater extent than the untreated control. Thus, HR inhibition of RAD51 may provide yet another mechanism of therapeutic target for the chemosensitization and radiosensitization of cervical cancer with RI-1. Collectively, our data demonstrated for the first time that inhibition of RAD51 suppressed the cervical cancer cell proliferation and the growth of cervical cancer xenografts by attenuating cell cycle transition, which could be a functional link between RAD51 and cyclin D1 and p21.